Impact of a theatre for development communication intervention on knowledge of childhood obesity among women in Nigeria - Michael Nnabundo NWABUZOR (Ianna Journal of Interdisciplinary Studies, 2020)
Background:  Although researchers agree that women are essential in the fight against childhood obesity, very little attempts, from developing countries like Nigeria, have been made to examine how to educate women on childhood obesity prevention.